Pengaruh Kompetensi Sumber Daya Manusia, Teknologi Informasi, dan Sistem Pengendalian Intern terhadap Kualitas Laporan Keuangan pada POLRESTA Pontianak Kota - Agustina, Monika; Haryono, Haryono; Astarani, Juanda; Rusliyawati, Rusliyawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of human resource (HR) competence, the use of information technology, and internal control systems on the quality of financial statements at Polresta Pontianak Kota. The research employed an associative approach using a survey method through questionnaires distributed to 35 respondents from divisions directly involved in financial management. Data analysis techniques included validity and reliability tests, classical assumption tests, multiple linear regression, as well as partial (t-test) and simultaneous (F-test) hypothesis testing. The results indicate that HR competence in accounting and internal control systems have a positive and significant effect on the quality of financial statements, while the use of information technology does not have a significant effect. Simultaneously, the three independent variables significantly affect the quality of financial statements, with a contribution of 41.9%, while the remaining 58.1% is explained by other factors outside this study. These findings emphasize the importance of improving HR competence and strengthening internal control systems to produce reliable, transparent, and accountable financial statements within Polresta Pontianak Kota.